Effects of MEMS material on designing a multi-band reconfigurable antenna - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz; Mohd Sahar, Norsuzlin; Zamani, Norasyikin (ACECER, 2009)
Abstract—In this work, two adjacent patches and MEMS switches are proposed a reconfigurable antenna that is capable of operating at several frequencies. Optimization of wing patches is done to obtain more than three resonant frequencies of the antenna by selecting the MEMS cantilever bridge materials. The study shows that the material of MEMS switches has influenced the performance of the antenna. SiN as MEMS bridge material makes the antenna to operate at 16.76 GHz, 23.56 GHz and 27.7 GHz at “OFF” states and at 23.5 GHz at “ON” states of the MEMS switches. A comparative study has done for Alumina, SiN, GaAs and Teflon as MEMS bridge materials. Further re-configurability can be obtained by varying the MEMS switch position. The design is performed by using 3D electromagnetic simulator HFSS considering ideal MEMS switches.